Recognition and Protection of Indigenous Peoples in Public Policy: Analysis of the Implementation of National Regulations - Ari Purwadi (Journal of Adat Recht, 2026)
Indigenous peoples are social groups with a long history, distinctive culture, and deep ties to their ancestral territories. In Indonesia, the recognition and protection of indigenous peoples has been normatively guaranteed through various legal instruments, ranging from the 1945 Constitution of the Republic of Indonesia to a number of sectoral laws and regulations. However, the implementation of these regulations in public policy practice still faces various structural, institutional, and cultural challenges. This article aims to analyze in depth the extent to which national regulations have provided real protection for indigenous peoples and to identify the obstacles that cause gaps between legal norms and realities on the ground. This research uses a normative juridical method with a legislative and conceptual approach, supplemented by empirical studies in the form of literature studies of various court decisions, reports from national and international institutions, and previous research. The results show that although the formal legal framework is quite comprehensive, its implementation is still hampered by unmanaged legal pluralism, weak synchronization between state institutions, minimal participation of indigenous peoples in the legislative process, and the hegemony of economic growth-based development that often sacrifices indigenous rights. This article concludes the need for comprehensive policy reform, including the creation of specific laws for indigenous peoples, strengthening of mentoring institutions, and the active involvement of indigenous peoples in every stage of public policy.